Nulle part chez nous - Pelletier, Sonia (CV Photo)

(untitled) (Les Productions Ciel variable, 2002)
Ivan Binet's images are impossible panoramic views that retrace the wanderings of the photographer-walker in different regions of Quebec. First sketched out during the shooting, these panoramas truly take form only during digital montage. Because of this, they constitute true "theatres of time and space"—the long time it takes for humans to transform landscapes, the time of walks condensed into images that stretch to allow the viewer to see more than the visual field permits in reality, multiple spaces to be seen simultaneously, forming a sort of directory of the experience of the vernacular landscape.